2015
DOI: 10.1016/j.jvs.2014.09.024
|View full text |Cite
|
Sign up to set email alerts
|

The bird beak configuration has no adverse effect in a magnetic resonance functional analysis of thoracic stent grafts after traumatic aortic transection

Abstract: Functional analysis showed no adverse long-term outcome of the bird beak configuration of stent grafts in the aortic arch after endovascular repair after blunt aortic injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…Our work also showed that the BBC does not appear to be associated with an increased risk of collapse/infolding or endograft thrombosis. This finding implies that the magnitude of the hemodynamic disturbances induced by the misalignment of the endograft, consistent with previous functional studies specifically performed in trauma patients, 12 may not per se induce complete endograft failure. Yet, displacement forces are greater in aneurysmal aortas compared with healthy aortas (ie, nondilated aortas such as in trauma patients) in zone 3, 7 and therefore clinical outcomes may vary based on the indication for TEVAR and the choice of the proximal landing zone.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our work also showed that the BBC does not appear to be associated with an increased risk of collapse/infolding or endograft thrombosis. This finding implies that the magnitude of the hemodynamic disturbances induced by the misalignment of the endograft, consistent with previous functional studies specifically performed in trauma patients, 12 may not per se induce complete endograft failure. Yet, displacement forces are greater in aneurysmal aortas compared with healthy aortas (ie, nondilated aortas such as in trauma patients) in zone 3, 7 and therefore clinical outcomes may vary based on the indication for TEVAR and the choice of the proximal landing zone.…”
Section: Discussionsupporting
confidence: 90%
“…Full texts of 517 articles relevant to the study were retrieved and reviewed; no randomized trials were found, so no quality exclusion criteria were applied. Ultimately, 21 articles 13,9,12,1429 were retrieved for qualitative analysis (Figure 2). Characteristics of the included studies are summarized in Table 1.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The occurrence of bird beak which was a risk factor for type Ia endoleak, depending on anatomy of the aortic arch and stiffness of the stents. 20 Boufi et al suggested that aortic angle of stent deployment zone more than 50° could be predictive of bird beak occurrence. 9 Many older generations of grafts were stiff and with big “z” rings and prone to lead to “bird beaking,” newer modifications helped significantly with the problem.…”
Section: Discussionmentioning
confidence: 99%
“…For further investigation a conventional angiography with pressure gradient measurement and a four-dimensional magnetic resonance imaging was performed. The quantitative flow measurements were obtained by means of a retrospective ECG gated cardiacphase resolved three-dimensional T1 weighted fast gradient echo acquisition [1,2].…”
Section: Case Blogmentioning
confidence: 99%